PENGARUH KREDIT UMKM, TENAGA KERJA DAN ENERGI LISTRIK TERHADAP PDRB TAHUN 2016-2018 - Dewi, Tania Tungga (Contemporary Studies in Economic, Finance and Banking, 2022)
Economic growth describes how the economic condition of the people. The process of economic growth is closely related to the process of producing goods and services. Indonesia as a country with 34 provinces certainly has different resources. This difference becomes a challenge to create a smooth flow in the production process to produce optimal economic growth. So this research is here to find out how the interaction between production factors that are used to produce output in goods and services. The research variables used are MSME credit, manpower, electrical energy, and gross regional domestic product. This study uses a quantitative approach. The analytical method used is unbalanced panel data with a time series for the 2016-2018 period and a cross-section of 34 provinces. The logarithmic regression method was used with the feasible generalized least square method. The regression analysis results show that partially MSME credit, manpower, and electrical energy have a positive and significant impact on gross regional domestic product. In addition, the independent variables (MSME credit, manpower, and electrical energy) in the model explain 0.999961 or 99% of the dependent variable (GRDP) while the rest is explained by other variables outside the model.